Blessed Social Networks: Analysis of the Campaign on Twitter of the Candidates for the Presidency of Mexico in 2018 - Sánchez-Nuevo, Lucía Alejandra (2022)
This paper studies the Twitter communication strategies of @lopezobrador_, @RicardoAnayaC, and @JoseAMeadeK, Mexican presidential candidates in 2018. The content of the candidates’ messages —the tweets, the copies and arts, hashtags, mentions and links— and their reach among users —measured in number of comments, retweets, likes and reproductions—is studied. Andrés Manuel López Obrador (AMLO) personalized his campaign, and its content generated the most positive sentiment. Ricardo Anaya Cortés (RAC) and José Antonio Meade Kuribreña (JAMK) attacked him and their content produced less engagement.